Tumbuhan Ficus L. (Moraceae) di hutan konservasi Prof. Soemitro Djojohadikusumo, PT. Tidar Kerinci Agung (TKA), Sumatera Barat - - Nur'aini; - Syamsuardi; Ardinis Arbain (Jurnal Biologi Universitas Andalas, 2013)
The floristic study of Ficus L. at conservation forest Prof. Soemitro Djojohadikusumo PT. Tidar Kerinci Agung (TKA) West Sumatera have been carried out from September 2012 to January 2013. Samples were directly collected during surveys along the tracks at the study area between 300 and 543 meter above sea levels. The samples were processed and identified at Herbarium ANDA, Biology Department. Twenty spesies of Ficus were identified. Each species could be distinguished by some specific morphological characters such as stipula, leaf frorm, waxy glands, and fruit type. We prepared description for each species and determination key of species level. Keywords: Ficus, forest conservation, floristic study, morfologycal character, palm oil planation and Species.